Korpuslinguistik - Kupietz, Marc; Schmidt, Thomas (Germanistische Sprachwissenschaft um 2020, 2018)
The study examines the concept of patterned language usage in scientific texts and, based on a data-led corpus analysis, describes scientific style at a formal and pragmatic level. With theoretical grounding in multiple linguistic sub-disciplines, the book makes a major contribution to text-type research, the discussion of standards, and to the study of writing